ØªÙ†Ù…ÙŠØ© ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„Ù…Ù„ØµÙ‚ Ø§Ù„ÙÙƒØ§Ù‡ÙŠ ÙÙŠ ØªØ±Ù‚ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¦Ø© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Ruwaida Hudatullah (Lughatu Ad-dhat, 2020)
ABSTRACT This research aims to develop correct and effective humorous poster methods on Arabic materials. The method used in this research is research and development with reference to the Borg and Gall development model with seven stages, viz., Research and data collection, planning, product development, expert validation testing, product review, product trial, and final product review. Based on the research results, it showed that the Arabic comic poster product is suitable for use in learning. In the results of the media experts' validation, it is known that the comic poster product is rated "good" with a score of 62 and the subject matter experts got a "good" category with a score of 63. The results of the students' response to the very Arabic humorous poster is 91%, then the students' response is rated very good. Then based on the student learning outcome data, the mean value of the learning outcomes on the pretest shows 49.25 <the post-test 72.75. The results of the correlation test show that the relationship between two large variables 0.010 with significant significance 0.976. This indicates that the relationship between the pre-test and post-test averages is strong and substantial. So that we can conclude that developing humorous poster methods is effective in promoting students' Arabic reading skills. Keyword: development of comic poster medium, skill of reading.